Experimental analysis of the characteristics of artificial vocal folds - Misun, Vojtech; Svancara, Pavel; Vasek, Martin (Journal of voice, 2011)
Specialized literature presents a number of models describing the function of the vocal folds. In most of those models, an emphasis is placed on the air flowing through the glottis and, further, on the effect of the parameters of the air alone (its mass, speed, and so forth). The article focuses on the constructional definition of artificial vocal folds and their experimental analysis. The analysis is conducted for voiced source voice phonation and for the changing mean value of the subglottal pressure. The article further deals with the analysis of the pressure of the airflow through the vocal folds, which is cut (separated) into individual pulses by the vibrating vocal folds. The analysis results show that air pulse characteristics are relevant to voice generation, as they are produced by the flowing air and vibrating vocal folds. A number of artificial vocal folds have been constructed to date, and the aforementioned view of their phonation is confirmed by their analysis. The experiments have confirmed that man is able to consciously affect only two parameters of the source voice, that is, its fundamental frequency and voice intensity. The main forces acting on the vocal folds during phonation are as follows: subglottal air pressure and elastic and inertia forces of the vocal folds' structure. The correctness of the function of the artificial vocal folds is documented by the experimental verification of the spectra of several types of artificial vocal folds.
Keywords: biologické modely; hlasové řasy; Air; vibrace; umělé orgány; Time Factors; časové faktory; lidé; tlak; Models, Biological; Rheology; Vocal Cords; Vibration; reologie; Artificial Organs; Phonation; Sound Spectrography; vzduch; fonace; Voice Quality; kvalita hlasu; Pressure; zvuková spektrografie; Humans